PENGARUH LOCUS OF CONTROL, GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI, INDEPENDENSI, PEMAHAMAN GOOD GOVERNANCE DA PROFESIONALISME TERHADAP KINERJA AUDITOR (Studi Empiris Pada Inspektorat Provinsi Riau, Kota Pekanbaru, Kota Dumai) - Muhammad Akbar S; Yuneita Anisma; Raja Adri Satriawan Surya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of Locus Of Control, leadershipStyle, Organizational Commitment, Independence, Understanding of GoodGovernance and Professionalism on auditor performance. The population in thisstudy were auditors who worked in the Riau Provincial Inspectorate office,Pekanbaru City, Dumai city as many as 77 auditors. Research sample usingcensus method. Based on these criteria, 60 auditors were selected as samples inthis study. This study uses multiple linear regression analysis which is used to testwhether the independent variables affect the dependent variable. Data analysisfor hypothesis testing was carried out with the Social Sciences Statistical Package(SPSS) ver 23.0. The results of this study indicate that locus of control ofgovernment auditors with t-test is 2.454, t-table 2.006 is significant 0.015. Theleadership style influences the auditor's performance with t-test 3.201, t-table2.006 is significant 0.02. Organizational Commitment has an effect on auditorperformance with t-test 2,443, t-table 2,006, significant 0,023. Understanding ofGood Governance influences auditor performance with t-test 2,278, t table 2,006,significant 0,047. While Independence does not play a role on auditorperformance with t-test -1.221, t-table 2.006 is significant 0.090 andProfessionalism does not affect auditor performance by t-test 1.394, t-table 2.006,significant 0.070.Keywords : Locus Of Control, Leadership Style , Organizational Commitment,Independency, Good Govrnance Comprehension, Profesionalism,Performance of Audiotors